First description of the male of Oonops nigromaculatus Mello-Leitão, 1944 (Araneae: Oonopidae) with the redescription of the female and new records - Grismado, Cristian J. (2009)
The male of Oonops nigromaculatus Mello-Leitão 1944 is described for the first time and the female is redescribed from recently collected specimens. New records from Argentina and Uruguay are provided.